The Impact of Quality, Value, Image, and Satisfaction on Customer Loyalty: a Quantitative Study - Erin (Journal of Multidisciplinary Issues, 2024)
Purposes - The purpose of this research is to examine the structural relationships between quality, value, image, satisfaction, and their combined influence on customer loyalty. The study aims to determine how these variables interact and to what extent quality affects loyalty both directly and indirectly through mediators like value and image. Methodology - This study employs a quantitative approach, using structural equation modeling (SEM) to analyze data collected from 250 respondents via a structured questionnaire. A Likert scale was utilized to measure responses across the variables. Reliability and validity assessments, including Cronbach’s alpha and Average Variance Extracted (AVE), were conducted to ensure robustness. Findings - The findings reveal that quality significantly impacts both value and image, which in turn influence satisfaction and loyalty. The results support the hypothesis that quality indirectly affects customer loyalty through perceived value and image. Image plays a critical role as a mediator, enhancing customer satisfaction and loyalty. Novelty - This research contributes to the existing literature by highlighting the complex, interrelated dynamics between quality, value, image, and satisfaction in driving customer loyalty. The study emphasizes the indirect effects of quality on loyalty through value and image, providing a deeper understanding of these mediating roles. Research Implications - The findings offer practical insights for businesses, suggesting that improving product or service quality can lead to better brand image and perceived value, which in turn boosts customer satisfaction and loyalty. Companies should focus on enhancing both quality and image to foster long-term customer retention and loyalty.